Development of Coaching Methods Through Instilling Islamic Values in Students at Tambakreja 07 Public Elementary School, South Cilacap District, Cilacap Regency - Eka Putrawati; Ine Kusuma Aryani (UM Purwokerto Press, 2023)
This study aims to (1) describe the initial conditions of the behavior process of students at SD Negeri Tambakreja 07 Cilacap Selatan; (2) to develop a coaching method based on Islamic values at SD Negeri Tambakreja 07 Cilacap Selatan; (3) to know the teacher's response to the implementation of the coaching method at SD Negeri Tambakreja 07 Cilacap Selatan; (4) to know students' responses to the implementation of coaching at SD Negeri Tambakreja 07 Cilacap Selatan. The type of research used in this study is the Research and Development (R&D) model of the Borg & Gall development. The product developed in this study is a coaching method by instilling Islamic values. After being developed, learning tools are tested for their effectiveness in improving character education. This research took place at SD Negeri Tambakreja 07, Cilacap Selatan District. The results showed that the coaching model development model for instilling Islamic values was in good category in the main field trials. After revising the model when the learning tools were applied, the results were in very good category in operational field trials. In addition, Islamic values are also included in the very good category in the experimental class. The coaching process encourages students to have Islamic values that are very relevant to current conditions. The development of a coaching model for inculcating Islamic values is suitable for application in SD Negeri Tambakreja 07.